Perilaku Pencarian Informasi Pemustaka - Arma, M. Arif; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper discusses about the behavior of information searcher in Public Library in Solok. (1) Describing how the behavior of information searcher in Public Library in Solok: (2) Describing how the availability of information in Public Library in Solok.This research uses qualitative and quantitative method by collecting the data through direct observing, and also direct interview with librarians. Further, the researcher also gives questioner to information searchers who come to Public Library in Solok. The data analysis is done descriptively. Based on the data analysis, it is concluded that; First, the behavior of information searchers can be seen the strategy used by the researcher. The source of information that is often used by visitors of the library is textbooks. The information searchers come to the library in order to do their paper or assignment, and also as a place to interact one another. Second, the availability of information is not enough. The visitors of the library stated that if the information is not found in Public Library in Solok, they will go to bookstores. The next is the using of additional equipments. In searching information in the library, most visitors will go directly to bookshelves and find the book by themselves. Keywords: Behavior; information searcher; user; library